Anesthetic Management for a Parturient with Facioscapulohumeral Muscular Dystrophy Undergoing Caesarean Section - Shrestha, S; Chan, YK; Razali, FN (Nepal Journal of Obstetrics and Gynaecology, 2016)
Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant muscle disorder characterized by progressive weakness and wasting of facial, shoulder girdle and upper arm muscles. Anesthetic management for the parturient with muscular dystrophy is very challenging for anesthesiologists because general as well as regional anesthesia may cause deleterious effect to the patient. We report a case of 28 years parturient with Facioscapulohumeral muscular dystrophy that underwent elective caesarean section under combined spinal epidural anesthesia. Intraoperative and postoperative period were uneventful however the motor block was prolonged. Regional anesthesia especially combined spinal epidural anesthesia can be safely used to provide anesthesia for caesarean section in patients with muscular dystrophy.